PETER F DRUCKER ON TECHNOLOGY - DRUCKER, PETER F. (BOSTON: HARWARD BUSINESS REVIEW PRESS, 2020)
Leading in a Technology-Driven WorldThe relationship of humans to technology is a ubiquitous theme in today's world of mobile devices, 24/7 internet access, and omnipresent digital business tools. The essays in this collection don't focus on a specific technology but on the challenges technology creates for management. In them Peter F. Drucker explores how managers can harness technology to enable workers to be more productive. In this collection he offers insights on:how technology affects the quality of lifethe difference between efficiency and productivitythe impact of technology on science and politicshow new technology affects not only what work can be done but also how it will be doneand other essential management topicsFilled with classic, evergreen advice$1 (B"Technology is not about tools; it deals with how man works"$1 (BPeter F. Drucker on Technology is essential reading for managers in the digital age.s
Keywords: Management -- Technological innovations; 20th century. TECHNOLOGY -- History; BUSINESS & ECONOMICS -- Management